Causes of maternal mortalities in educational hospitals of Zahedan University of Medical Sciences with ICD-MM approach from 2011 to 2018 - Afsaneh Karimi; Farzaneh Shahbakhsh; Sonia Nourouzi-Chegani; Jahanpour Alipour (Mashhad University of Medical Sciences, 2021)
Introduction: The WHO application of ICD-10 to deaths during pregnancy, childbirth and the puerperium (ICD-MM) leads to a better understanding of maternal mortalities. This study was performed with aim to determine the causes of pregnant mothers' mortalities in the educational hospitals of Zahedan University of Medical Sciences using the ICD-MM. Methods: In this cross-sectional study which was conducted in 2019, 107 records of pregnant mothers' mortalities occurred in Zahedan in 2011-2018 were studied. The causes of deaths were coded using ICD-MM with three volumes of ICD-10 (The 10th revision of the International Statistical Classification of Diseases and Related Health Problems). Data were recorded in the data collection form and were analysed by SPSS software (version 15). Results: During 8-years of the study period, 107 cases of maternal mortality occurred. The maternal mortality ratio in the study population was 254 per 100,000 live births and the mean age of dead pregnant mothers was 31.7 ± 7.3 years. Direct causes with 73.8%, indirect causes with 20.6%, unspecified causes with 2.8% and coincidental causes with 2.8% were responsible for maternal mortalities. Other obstetric complications with 22.4%, obstetric hemorrhage and non-obstetric complications with 20.6% had the most values in maternal mortalities between nine groups listed in the ICD-MM. Conclusion: Postpartum coagulation defects, puerperal sepsis, and other blood diseases and blood-forming organs and certain disorders involving the immune mechanism were three main causes of maternal mortalities in this study. Therefore, predicting hemorrhage and preparing to control it, such as rapid access to blood and its products, screening of pregnant mothers with blood diseases and providing them with specialized training and care, as well as paying more attention to postpartum care for at least 42 days after delivery, especially in cases of postpartum hemorrhage and infection, could be effective in preventing more maternal mortality.